Bactericidal activity of gallic acid against multi-drug resistance Escherichia coli. (December 2022) - Tian, QiMing; Wei, SiMin; Su, HongRui; Zheng, ShuMei; Xu, ShuYa; Liu, MingJiang; Bo, RuoNan; Li, JinGui
Abstract: The continuous emergence of multidrug-resistant (MDR) bacteria has posed an increasingly serious public health threat which urges people to develop some alternatives. Gallic acid (GA) is a natural ingredient in many traditional Chinese medicines, which has many biological activities, such as antibacterial, and antiseptic. Here, clinical isolates of MDR Escherichia coli ( E. coli ) were used to evaluate the antibacterial effect of GA and the underlying mechanism. The results revealed that GA exerted bactericidal activity and inhibited the formation of bacterial biofilm. GA enhanced the activities of ceftiofur sodium or tetracycline against E. coli, and facilitated antibiotic accumulation in bacteria. Further analysis of morphological alterations and efflux pump gene expressions confirmed that GA damaged outer and inner membranes, and suppressed the mRNA expressions of acrA, acrB, tolC, acrD and acrF involved in membrane permeability. In addition, GA showed protective effects against bacterial infection and improved the survival rates of Galleria mellonella and BALB/c mice. These data highlight a better understanding of GA against bacteria and provide an alternative strategy for MDR bacterial infection. Graphical abstract: Image 1 Highlights: Gallic acid (GA) exerted rapid bactericidal activity and had inhibitory effect on bacterial biofilm. GA exhibited synergy with antibiotics and facilitated antibiotic intracellular accumulation. GA damaged the integrity of bacterial outer/inner membrane and significantly decreased the efflux pump genes expression. GA was effective in Galleria mellonella and mouse infection models.